Study of the Effect of Eucalyptus Plant Extract in Preventing the Growth of Pathogenic Bacteria Causing Tonsillitis in Children - Sameer Jaaz, Widad; Jwad Abid Al Hussein, Hassanain (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates the inhibitory potential of the extract of water and alcohol from the eucalyptus plant in preventing the growth of two types of pathogenic bacteria: Staphylococcus aureus (+ ve) and Proteus mirabilis gram (-ve), which causes tonsillitis in children. By taking bacterial isolates from the samples of tonsils of children and bacterial growth in secondary isolates of subcultures and the effect of different concentrations (10, 10-1, 10-2, 10-4) for both water and alcohol extraction from the eucalyptus plant. The filter paper is then immersed in these solutions and left to dry and then placed in dishes containing isolated bacteria and placed in the incubator for two days at a temperature of 37 degrees. Thus, inhibitory levels of both types of extracts were observed in preventing the growth of pathogenic bacteria that cause tonsillitis in children aged 5-10 years.